TUMOR MARKERS IN OVARIAN CANCER - Adina-Elena Nenciu; C. G. Nenciu; R. Fodoroiu; Florica Șandru; M.C. Dumitrașcu (Journal of Surgical Sciences, 2020)
Even if today’s society is rapidly evolving there is still much that can be done. This applies in the oncological field. One of the main female health problems worldwide is represented by the gynecological cancers. Ovarian cancer is the main cause of mortality among women with gynecological cancers. Although its prevalence is lover compared to breast, uterine or cervical cancer, the mortality and morbidity rates are significantly higher. The first step in the management of ovarian cancer is represented by regular screening and rapid diagnosis. One of the most important tolls is represented by serological markers dosage in order to estimate the type of tumor before the gynecological specific intervention. There is a real need to identify correctly the ovarian cancer as early as possible in order to obtain the favorable prognosis that comes with the diagnosis in earlystage. Most of the ovarian cancers (above 90%) are represented by carcinomas which are frequently diagnosed in advanced stages. The roles of the biomarkers are to indicate the malignancy of an ovarian tumor and to predict the relapse risk. The aim of this paper is to update the indications regarding the usage of serological markers in ovarian cancers and the importance of using them for our patients.